The Role of Societal Change toward Adolescent Suicide in Japan: Phenomenological Analysis on 12 Suicidal Teens Film by Yukihiko Tsutsumi - Salma Nabila; Susy Ong (IZUMI, 2021)
Suicide cases are still a big challenge for Japan, even though in the 21st century, the government began to pay attention to and follow up on this phenomenon. While Japan's suicide rate among adults is declining, the rate in minors increased, and suicide is the highest cause of death for those under 20. This research reveals the problems and factors around suicidal teens in Japan through twelve characters' stories in 12 Suicidal Teens Film. To understand this film, what meaning that brought to discussion requires interpretation. Paul Ricoeur said that text or work is a dialogue to reveal the dimensions of reality in the phenomenological approach. The suicide motives expressed by 12 teenagers in the film 12 Suicidal Teens could be common. However, there are several factors such as religion, culture, social, even economic trends that could influence teenagers to commit suicide. The result shows that the social changes in Japan put pressure not only on adults but also on the lives of the youth. Also, information that is increasingly easy to obtain by anyone can become a boomerang for society because people can learn from what this information says.